Design and evaluation of security protocols for wireless vehicle communications - Dong, Dong (2012)
Vehicular ad-hoc networks (VANET) provide communication tunnels for various applications for safety, traffic condition, driving assistance and infotainment. In VANET, network topology changes constantly as vehicles move in and out of wireless range quickly. Therefore, there is a need for a fast and secure authentication process for communications between vehicles and a roadside station.